2020
DOI: 10.1029/2020wr027965
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Wettability and Surface Roughness on Fluid Displacement and Capillary Trapping in 2‐D and 3‐D Porous Media: 2. Combined Effect of Wettability, Surface Roughness, and Pore Space Structure on Trapping Efficiency in Sand Packs and Micromodels

Abstract: A comprehensive understanding of the combined effects of surface roughness and wettability on the dynamics of the trapping process is lacking. This can be primarily attributed to the contradictory experimental and numerical results regarding the impact of wettability on the capillary trapping efficiency. The discrepancy is presumably caused by the surface roughness of the inner pore-solid interface. Herein, we present a comparative μ-CT study of the static fluid-fluid pattern in porous media with smooth (glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 33 publications
(70 reference statements)
9
48
0
Order By: Relevance
“…From the works of Cieplak and Robbins (1988) and Zulfiqar et al. (2020), the contact angle of our microfluidics is larger than the critical contact angle, and the unstable flooding is expected. However, as shown in Figure 3, we observe the compact displacement in uniform porous media (see Figures 3a 5 , 3a 6 , 3b 5 , and 3b 6 ).…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…From the works of Cieplak and Robbins (1988) and Zulfiqar et al. (2020), the contact angle of our microfluidics is larger than the critical contact angle, and the unstable flooding is expected. However, as shown in Figure 3, we observe the compact displacement in uniform porous media (see Figures 3a 5 , 3a 6 , 3b 5 , and 3b 6 ).…”
Section: Resultsmentioning
confidence: 73%
“…Recently, Geistlinger and Zulfiqar (2020) and Zulfiqar et al. (2020) performed fluid‐displacement experiments in 2D and 3D porous media to further explore the wettability effect. They found that the critical contact angle for the pattern transition is significantly affected by the pore space structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on capillary trapping in natural sands (estimated contact angle about 20°; Geistlinger et al, 2015) show residual gas trapping of about 15%. Future research will investigate the impact of grains with rough surface and irregular geometry on the Cieplak‐Robbins transition and will be published in Part 2 of the study (Zulfiqar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%